2020
DOI: 10.3389/fnmol.2020.00020
|View full text |Cite
|
Sign up to set email alerts
|

Plasma BDNF and TrkB mRNA in PBMCs Are Correlated With Anti-depressive Effects of 12-Weeks Supervised Exercise During Protracted Methamphetamine Abstinence

Abstract: The aim of this study was to evaluate the potential neurotrophic factors and expression of neurotrophin receptors in peripheral blood mononuclear cells linked with the antidepressant action of exercise intervention during protracted methamphetamine (METH) abstinence. Materials and Methods: A total of 72 male METH addicts, including 47 individuals with depression and 25 individuals without depression, were recruited in this study. Individuals with depression were divided into the depression control group and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…It has not been reported that treadmill exercise can improve anxiety-like symptoms in METH acute withdrawal by counteracting the central inflammation induced by METH. Consistent with the results of a previous clinical study ( Yang J. et al, 2020 ), our behavioral results demonstrated that moderate-intensity treadmill exercise can alleviate anxiety-like symptoms during acute METH withdrawal in mice. Numerous studies in related fields have shown that exercise can regulate microglial activation and the inflammatory response in neurodegenerative diseases, such as Alzheimer’s disease ( Lu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…It has not been reported that treadmill exercise can improve anxiety-like symptoms in METH acute withdrawal by counteracting the central inflammation induced by METH. Consistent with the results of a previous clinical study ( Yang J. et al, 2020 ), our behavioral results demonstrated that moderate-intensity treadmill exercise can alleviate anxiety-like symptoms during acute METH withdrawal in mice. Numerous studies in related fields have shown that exercise can regulate microglial activation and the inflammatory response in neurodegenerative diseases, such as Alzheimer’s disease ( Lu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…exercise training regime improved their aerobic capacity, muscle strength, endurance, and percentage of body fat, all of which correlates with reduction of depression symptoms (Dolezal et al, 2013;Haglund et al, 2015). Studies by Haglund et al (2015), Rawson et al (2015), and Yang et al (2020) showed that exercise also attenuates METH-induced depression and anxiety symptoms in early recovery and METH-abstinent individuals. Also, exercise improves the quality of life of METH users (as measured by questionnaires) through enhancement of psychological health, as well as their social relationships (Muller & Clausen, 2015).…”
Section: Individuals With Meth Dependence Who Engaged In An Establishedmentioning
confidence: 94%
“…For example, exercise reduces METH‐induced deficits on dopamine receptors 1 and 3 in the striatal area, both of which are important in the reward system (Robertson et al., 2016). Another study showed that exercise counteracts METH withdrawal‐induced increases in BDNF plasma levels, and TrkB mRNA in peripheral blood mononuclear cells, which correlates with attenuation of depression and anxiety behavior (Yang et al., 2020). In addition, functional magnetic resonance neuroimaging studies showed that the efficiency and direction of information transmission between left and right prefrontal cortices, and/or left and right motor cortices were lower in female subjects with METH dependencies in training (practicing kickboxing exercise) and resting states, compared with control groups.…”
Section: Effects Of Exercise On Substance Use Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Using functional near-infrared spectroscopy (fNIRS) and heart rate signal evaluation, researchers found that physical training can affect brain functional connectivity in METH-dependent subjects to a certain extent [ 87 , 88 ]. Recent studies have further demonstrated that exercise can reduce depression and anxiety during withdrawal in patients with long-term METH exposure, possibly through mechanisms related to plasma BDNF and TrkB levels in peripheral blood mononuclear cells [ 89 ].…”
Section: Exercise Effectively Interferes With Meth Abusementioning
confidence: 99%